A research protocol for testing relationships between nurse workload, missed nursing care and neonatal outcomes: the neonatal nursing care quality study. (29th October 2014) - Tubbs‐Cooley, Heather L.; Pickler, Rita H.; Mark, Barbara A.; Carle, Adam C.
Abstract Aim We describe an innovative research protocol to test the role of missed nursing care as a mediator of the association between nurse workload and patient outcomes in the neonatal intensive care unit. Background Increases in nurses' workloads are associated with adverse patient outcomes in neonatal intensive care settings. Missed nursing care is a frequently hypothesized explanation for the association between workload and outcomes. Few studies to date have tested missed care as a variable that mediates the workload–outcomes relationship. Design We use a longitudinal, observational study design. Methods We will recruit approximately 125 nurses (80% of target population) providing direct patient care in one neonatal intensive care unit. Four, 6‐week data collection cycles occur over 1 year. At the end of every shift, nurses report on their workloads and the frequency with which specific patient care activities were missed for each infant cared for during the shift. Infant‐specific nurse reports of missed care are linked to shift‐level infant outcomes data extracted from the electronic health record. Funding for the study began in July 2012; Research Ethics Committee approval was granted in December 2012. Discussion Missed care may explain the effects of nurse workload on patient outcomes. This research will generate preliminary evidence regarding the causal relationships among nurses' workloads, missed care and infant outcomes that we will confirm in a future multi‐site study.